Involvement of the posterior limb of the internal capsule independently predicts the prognosis of patients with basal ganglia and thalamic hemorrhage - Sohan Gupta; Mengxuan Xiao; Na Liu; Na Liu; Yunxiao Zhao; Xiaolin Zhao; Yunqiang Huang; Yongming Wu; Zhenzhou Lin; Zhong Ji; Haihao Xu; Minzhen Zhu; et al. (Frontiers in Neurology)
BackgroundIntracerebral hemorrhage (ICH) is the most lethal and devastating subtype of stroke. Basal ganglia hemorrhage and thalamic hemorrhage are the most common types of ICH, accounting for 50–70% of all ICH cases, leading to disability and death, and it involves the posterior limb of the internal capsule to varying degrees. In this study, we investigated the impact of varying degrees of the involvement of the posterior limb of the internal capsule on the prognosis of patients with basal ganglia and thalamic ICH and assessed whether it improves the predictive accuracy of the max-ICH score, an existing scale for ICH functional outcome.MethodsThis is a multicenter, retrospective, observational study. We graded the involvement of the posterior limb of the internal capsule according to the degree of compression and injury (called iICH, ranging from 0 to 4). An unfavorable outcome was defined as a 90-day modified Rankin Scale (mRS) of > 2. Multivariate logistic regression analysis was used to identify independent risk factors associated with unfavorable prognosis. The discrimination was verified using receiver operating characteristic curve (ROC) analysis, while the calibration was verified by the Hosmer-Lemeshow test.ResultsOf the 305 patients included, 188 from Nanfang Hospital were assigned to the development cohort, and 117 from Heyuan People's Hospital and Huadu District People's Hospital were assigned to the validation cohort. In the development cohort, iICH was identified as an independent factor of a 90-day unfavorable outcome, and the area under the ROC (AUC) was 0.774. When combined with the iICH, the AUC of max-ICH was significantly elevated from 0.816 to 0.866. Comparable results were found in the validation cohort.ConclusionsIncreased involvement of the posterior limb of the internal capsule is associated with a worse outcome in patients with basal ganglia and thalamic ICH.